Transcriptome data analysis provides insights into the conservation of Michelia lacei, a plant species with extremely small populations distributed in Yunnan province, China - Yang Liu; Lei Cai; Weibang Sun (BMC Plant Biology, 2024)
Abstract Background Michelia lacei W.W.Smith (Magnoliaceae), was classified as a Plant Species with Extremely Small Populations (PSESP) by the Yunnan Provincial Government in both action plans of 2012 and 2021. This evergreen tree is known for its high ornamental and scientific value, but it faces significant threats due to its extremely small population size and narrow geographical distribution. The study aims to understand the genetic structure, diversity, and demographic history of this species to inform its conservation strategies. Results The analysis of transcriptome data from 64 individuals across seven populations of M. lacei identified three distinct genetic clusters and generated 104,616 single-nucleotide polymorphisms (SNPs). The KM ex-situ population, originating from Longling County, exhibited unique genetic features, suggesting limited gene flow. The genetic diversity was substantial, with significant differences between populations, particularly between the KM lineage and the OTHER lineage. Demographic history inferred from the data indicated population experienced three significant population declines during glaciations, followed by periods of recovery. We estimated the effective population size (Ne) of the KM and OTHER lineages 1,000 years ago were 85,851 and 416,622, respectively. Gene flow analysis suggested past gene flow between populations, but the KM ex-situ population showed no recent gene flow. A total of 805 outlier SNPs, associated with four environmental factors, suggest potential local adaptation and showcase the species' adaptive potential. Particularly, the BZ displayed 515 adaptive loci, highlighting its strong potential for adaptation within this group. Conclusions The comprehensive genomic analysis of M. lacei provides valuable insights into its genetic background and highlights the urgent need for conservation efforts. The study underscores the importance of ex-situ conservation methods, such as seed collection and vegetative propagation, to safeguard genetic diversity and promote population restoration. The preservation of populations like MC and BZ is crucial for maintaining the species' genetic diversity. In-situ conservation measures, including the establishment of in-situ conservation sites and community engagement, are essential to enhance protection awareness and ensure the long-term survival of this threatened plant species.